Respuesta :
Answer:
The zeros of the quadratic polynomial are
[tex]x=\frac{15\sqrt{5}}{10}[/tex] and [tex]x=-\frac{3\sqrt{5}}{10}[/tex]
The relationship between its zeroes and coefficients in the procedure
Step-by-step explanation:
step 1
Find the zeros
we know that
The formula to solve a quadratic equation of the form [tex]ax^{2} +bx+c=0[/tex] is equal to
[tex]x=\frac{-b(+/-)\sqrt{b^{2}-4ac}} {2a}[/tex]
in this problem we have
[tex]4\sqrt{5}x^{2}-24x-9\sqrt{5}=0[/tex]
so
[tex]a=4\sqrt{5}\\b=-24\\c=-9\sqrt{5}[/tex]
substitute in the formula
[tex]x=\frac{-(-24)(+/-)\sqrt{-24^{2}-4(4\sqrt{5})(-9\sqrt{5})}} {2(4\sqrt{5})}[/tex]
[tex]x=\frac{24(+/-)\sqrt{-24^{2}-4(4\sqrt{5})(-9\sqrt{5})}} {8\sqrt{5}}[/tex]
[tex]x=\frac{24(+/-)\sqrt{1,296}} {8\sqrt{5}}[/tex]
[tex]x=\frac{24(+/-)36} {8\sqrt{5}}[/tex]
[tex]x=\frac{24(+)36} {8\sqrt{5}}=\frac{15\sqrt{5}}{10}[/tex]
[tex]x=\frac{24(-)36} {8\sqrt{5}}=-\frac{3\sqrt{5}}{10}[/tex]
step 2
Find the sum of the zeros and the product of the zeros
Sum of the zeros
[tex](\frac{15\sqrt{5}}{10})+(-\frac{3\sqrt{5}}{10})=\frac{12\sqrt{5}}{10}=\frac{6\sqrt{5}}{5}[/tex]
Product of the zeros
[tex](\frac{15\sqrt{5}}{10})*(-\frac{3\sqrt{5}}{10})=-\frac{9}{4}[/tex]
step 3
Verify that
Sum of the zeros= -Coefficient x/Coefficient x²
Coefficient x=-24
Coefficient x²=4√5
substitute
[tex]\frac{6\sqrt{5}}{5}=-(-24)/4\sqrt{5}\\ \\\frac{6\sqrt{5}}{5}=\frac{6\sqrt{5}}{5}[/tex]
therefore
the relationship is verified
step 4
Verify that
Product of the zeros= Constant term/Coefficient x²
Constant term=-9√5
Coefficient x²=4√5
substitute
[tex]-\frac{9}{4}=(-9\sqrt{5})/4\sqrt{5}\\ \\-\frac{9}{4}=-\frac{9}{4}[/tex]
therefore
the relationship is verified